KARAKTERISTIK BIOKOMPOSIT SERAT KELAPA BERPENGUAT UNSATURATED POLYESTER RESIN DENGAN PENAMBAHAN GUGUS SILANE - Marcella, Putri Andi; Fahmy, Putri Nadya; Mulana, Farid; RCL, Nasrullah (STKIP PGRI Situbondo, 2024)
Natural fibers are an alternative to synthetic materials that can be used as fillers in biocomposites due to their inherent biodegradability so that it has the potential to be put to good use. In this study, biocomposites were made using raw materials from natural waste, namely coconut fibers. These fibers are combined with unsaturated polyester resin. The addition of these functional groups can be done by using a coupling agent, it useful for strengthening the bond between the matrix and filler. The coconut fibre treatment process involved applying silane at various concentrations, either directly to the fibres or to the unsaturated polyester resin, using different methods to optimize adhesion. The samples will be analyze using Fourier Transform Infra-Red (FTIR) to determine their functional groups and physical properties analysis using predetermined standards. The addition of silane coupling agent makes the composite fibre-matrix interaction stronger, as indicated by the appearance of new peaks in the FTIR spectra. Furthermore, the results demonstrate that its inclusion can increase the density of composites across various treatments.